The Influence of Leadership Style on Employee Performance at Nusantara Surya Sakti (NSS) Soppeng Branch - Umar Umar; Ibrahim Ibrahim (GENTARA: management and accounting research, 2025)
This study aims to examine the effect of leadership style on employee performance at Nusantara Surya Sakti (NSS) Soppeng. The research utilizes a descriptive approach combining qualitative and quantitative methods, including interviews, questionnaires, and literature review. A total of 31 employees from NSS Soppeng participated in the study. The data were analyzed using simple linear regression to assess the relationship between leadership styles and employee performance. The results reveal a significant positive effect of leadership style on employee performance, with leadership behavior influencing productivity, job satisfaction, and task completion. This study contributes to the understanding of how different leadership styles impact employee motivation and performance in the Indonesian automotive industry. However, the study is limited by its focus on one branch of NSS and a small sample size. The findings suggest that improving leadership practices, especially in decision-making and employee engagement, can enhance performance. Further research is recommended to explore additional factors influencing performance, such as communication skills and organizational culture, and to extend the study across multiple branches for generalizability